2017
DOI: 10.22219/jpbi.v2i3.3875
|View full text |Cite
|
Sign up to set email alerts
|

Perception and preferences teachers in Tana Tidung district based on lesson study applications by the motivation and attitude for professionalism development of boundary region teacher

Abstract: ABSTRAK ABSTRACT One of the teacher professional development activities is made papers in the field of education. Tana Tidung Department of Education early 2015 has initiated a program professionalism of teachers through Lesson study. This activity is one way of professional guidance for educators and improve the quality of the learning process through collaborative learning assessment and sustainable based on the principles of collegiality and mutual learning to build a learning community around the school an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Although, in core activities and beyond, teachers felt more comfortable when teaching. The results of this research are in line with several previous studies (Norhanah, 2022;Vlorensius et al, 2016), which revealed that model teachers tend to feel nervous when carrying out open-class activities because there are quite a lot of observers observing.…”
Section: Retrospective Analysis/see What Is the Form Of Revision Of T...supporting
confidence: 91%
“…Although, in core activities and beyond, teachers felt more comfortable when teaching. The results of this research are in line with several previous studies (Norhanah, 2022;Vlorensius et al, 2016), which revealed that model teachers tend to feel nervous when carrying out open-class activities because there are quite a lot of observers observing.…”
Section: Retrospective Analysis/see What Is the Form Of Revision Of T...supporting
confidence: 91%